2019
DOI: 10.1016/j.compstruct.2019.02.068
|View full text |Cite
|
Sign up to set email alerts
|

The high strain rate tension behaviour of pseudo-ductile high performance thin ply composites

Abstract: In this study the effect of strain rate in tension on two different types of thin-ply pseudo-ductile laminates is reported. These comprised Unidirectional (UD) and quasi-isotropic (QI) hybrids made from low strain thin-ply carbon/epoxy and high strain glass/epoxy prepreg and all-carbon laminates made from thin-ply [±ϴ/0]s laminates referred to as angle-ply (AP) composites. Laminates were designed and subjected to a range of cross-head speeds from 2 mm/min (0.0003 s-1) to 10 m/s (100 s-1). The designed laminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Consequently, the discrepancy in strain rate did not influence the progression of damage. Previous research [19] has already examined the impact of strain rate, revealing only minor alterations in failure mechanisms at high speeds (5-10 m/s). As a result, we do not anticipate any discernible effects on the failure mechanisms due to the slight difference in loading rates (2 mm/min vs. 1 mm/min).…”
Section: Test Proceduresmentioning
confidence: 99%
“…Consequently, the discrepancy in strain rate did not influence the progression of damage. Previous research [19] has already examined the impact of strain rate, revealing only minor alterations in failure mechanisms at high speeds (5-10 m/s). As a result, we do not anticipate any discernible effects on the failure mechanisms due to the slight difference in loading rates (2 mm/min vs. 1 mm/min).…”
Section: Test Proceduresmentioning
confidence: 99%
“…In order to study the suitability of PDH composites in real-life applications, these composites were investigated at high strain rates and off-axis loadings. QI and UD PDH composites were seen to have excellent pseudo-ductile responses both in quasi-static and high strain rates through fragmentation and stable pull-out of the carbon layers [14]. An increase in the off-axis angle of the QI laminates did cause small changes in the pseudo-ductile strain and maximum stress values, however, the laminates still showed a pseudo-ductile response [15].…”
Section: Introductionmentioning
confidence: 98%
“…[20] Therefore, carbon/glass hybridization can introduce plastic deformation by increasing the percent elongation (pseudo ductility) in the CFRPC composites and suppress their catastrophic failure mode. [22,23] Over the years, pseudo ductile hybrid composites with two different types of fibers have been achieved in three distinct ways: (1) interlayer, (2) intralayer and (3) fiber-by-fiber or intrayarn configurations. [24] A number of studies have been reported over the years to achieve pseudo ductility in FRPCs.…”
Section: Introductionmentioning
confidence: 99%